1157 Emergency preparedness among the farm workers while performing the farm activities during summer months. (24th April 2018) - Kesarwani, K; Sharma, P
Abstract : Introduction: India being mainly an agricultural country, economy and further its growth purely depends on farming, making agriculture as most preferred occupation nationwide. The exposure of farm workers to this extreme weather condition especially during the summer months (March-June) is just hampering their health. Worsening of health is more prominent because most of farm activities are carried out manually under direct heat exposure and lack of awareness among the farm workers regarding the health hazards and even the un-availability of the protective methods. The combination of manual farm activities and heat exposure is a health, environmental and occupational issue, which need serious concern. The study focused on finding out the adaptive methods adopted by the farm workers. Methods: The study was undertaken to find out the adaptive methods adopted by the farm workers while accomplishing the farm activities during month of March to June and develop PPE to protect them from heat stress. Results: It was revealed that 98.9 percent of the farmers increased daily water intake, whereas, 27.8 percent increased liquid diet in their daily food intake. Regular intake of the herbal coolant was also very prominent among them, such as jal jeera, mint, cucumber, onion garlic, lemon water, curd, etc., as these coolants were easily available to farmers. With reference to clothing habit wearing loose cloth was only adopted by 47 percent. The data regarding the protective methods to be adopted while performing the farm activities, it was revealed that sunglass, hat, gloves, umbrella scarf etc. were least adopted by them due to their poor feasibility while performing the task. Conclusion: Thus, with the pace with which global average temperature is rising, emergency preparedness is very important among outdoor workers in order to keep themselves protected from heat stress. Creating awareness and developing PPE to safeguard is important.